2014
DOI: 10.1155/2014/349718
|View full text |Cite
|
Sign up to set email alerts
|

Induced Effects of Transcranial Magnetic Stimulation on the Autonomic Nervous System and the Cardiac Rhythm

Abstract: Several standard protocols based on repetitive transcranial magnetic stimulation (rTMS) have been employed for treatment of a variety of neurological disorders. Despite their advantages in patients that are retractable to medication, there is a lack of knowledge about the effects of rTMS on the autonomic nervous system that controls the cardiovascular system. Current understanding suggests that the shape of the so-called QRS complex together with the size of the different segments and intervals between the PQR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
11
0
3
Order By: Relevance
“…Amounts of studies have shown that high-frequency stimulation increases cortical excitability, whereas low-frequency stimulation decreases neuronal excitability 11 12 . Recently, studies also demonstrated that TMS might affect the cardiac rhythm by modulating the autonomic nervous system 7 . Scherlag et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amounts of studies have shown that high-frequency stimulation increases cortical excitability, whereas low-frequency stimulation decreases neuronal excitability 11 12 . Recently, studies also demonstrated that TMS might affect the cardiac rhythm by modulating the autonomic nervous system 7 . Scherlag et al .…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS), a neurostimulation and neuromodulation technique based on the principle of electromagnetic induction of an electric field in the brain, has been proposed for treatment of a variety of neurological disorders. Previous studies has shown that TMS might mediate the cardiac rhythm by modulating the autonomic nervous system 7 . Scherlag et al .…”
mentioning
confidence: 99%
“…An Italian study reported that LF rTMS of the PFC induces a slight parasympathetic activation (highlighted by a significant bradycardia), and no changes in the sympathetic function [ 45 ]. Conversely, HF rTMS producing cortical excitation especially when applied to the primary motor cortex has been supposed to evoke cardiac responses mediated by connections in the brain cortex with the cardiac-related centers of the CNS (e.g., increase in heart rate) [ 46 ]. In our study, contrary to expectations, neither significant changes in blood pressure nor hypertensive crisis were observed in obese patients receiving HF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The IMFs having most of the power in the autonomic frequency band were retained. The IMFs were then aggregated accordingly to the HF (0.15–0.45 Hz) and LF (0–0.15 Hz) ranges related to the parasympathetic and sympathetic systems activity (Cabrerizo et al, 2014; Figure 3). A CRQA was performed (Marwan and Kurths, 2002; Marwan, 2016) to assess the similarity between the dynamics of the parasympathetic and sympathetic processes by comparing the interaction between the LF and the HF components in the phase space.…”
Section: Methodsmentioning
confidence: 99%